TEST OF ANAEROBIC POTENCY MICROCONTROLLED FOR PLAYERS OF VOLLEYBALL: A PROPOSAL OF VALIDATION (Fiep Bulletin - online, 2014)
The specificity of the sport gesture is a constant concern during the planning of the training sessions, in all sports, and it is based in that new tendency that in this work has the objective of validating a test of anaerobic potency, respected the specificities of the displacements and actions of the volleyball. 7 male volleyball players took part in the study, who where 18 ± 0 years of age, 1,86 ± 0,07 cm of stature, 68,5 ± 0,71 of body mass and 12,55 ± 1,84 of percentile of fat, from the teen category of the Paraiba's main team. For the collect of data, it was used the adapted protocol of Sousa and Pellegrinotte (2005) and RAST (Running-based Anaerobic Test). The used variables were: speed (m/s), height (cm) of the vertical jump (coach gesture of the attack), running total distance, changes of direction, and number of vertical jumps. In the plan of analysis of the data, the descriptive statistics was used: average, standard deviation, maximum and minimum value, Alpha of Crombach, variation coefficient. The averages of the maximum and medium potency, for VTP and RAST, were, respectively of 2400,9±719,3W and 852,9±166,0W; 1874±588,8W and 687,3±114,8W. In this study it was concluded that VTP measured the capacity of performance of the potency and it was technically needed to register the athletes' performance.
Keywords: Tests; volleyball; potency